2021
DOI: 10.1158/1078-0432.ccr-20-2974
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Intratumoral Lymphoid Aggregates Correlate with Survival Following Treatment with a Neoadjuvant and Adjuvant Vaccine in Patients with Resectable Pancreatic Adenocarcinoma

Abstract: Purpose: Immunotherapy is currently ineffective for nearly all pancreatic ductal adenocarcinomas (PDAC), largely due to its tumor microenvironment (TME) that lacks antigen-experienced T effector cells (Teff). Vaccine-based immunotherapies are known to activate antigen-specific Teffs in the peripheral blood. To evaluate the effect of vaccine therapy on the PDAC TME, we designed a neoadjuvant and adjuvant clinical trial of an irradiated, GM-CSF-secreting, allogeneic PDAC vaccine (GVAX). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…The delayed proliferation or increase in the live cell number of labeled and unlabeled CAR T-cells observed only on day 5 timepoint was expected because Zheng et al . 2020 already demonstrated that the BB3z signaling domain contributed to limited proliferation of CAR T-cells with humanized Lym-1, and replacing BB3z with DAP12 restored expansion capacity in the transduced T-cells 22 . Interestingly, the 89 Zr-oxine labeled CAR T-cells used in the in vivo experiments had higher cell specific activities and showed a transient decrease in %viability on day 1 and an eventual enhanced %viability and live cell count on day 5 compared to unlabeled CAR T-cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The delayed proliferation or increase in the live cell number of labeled and unlabeled CAR T-cells observed only on day 5 timepoint was expected because Zheng et al . 2020 already demonstrated that the BB3z signaling domain contributed to limited proliferation of CAR T-cells with humanized Lym-1, and replacing BB3z with DAP12 restored expansion capacity in the transduced T-cells 22 . Interestingly, the 89 Zr-oxine labeled CAR T-cells used in the in vivo experiments had higher cell specific activities and showed a transient decrease in %viability on day 1 and an eventual enhanced %viability and live cell count on day 5 compared to unlabeled CAR T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Second generation CAR T-cells were constructed following procedures in Zheng et al . 21 , 22 by transducing human primary T-cells with huLym-1-A-BB3z-CAR encoding lentivirus. The CAR sequences consisted of a binding domain (anti huLym-1-A ScFv), hinge and transmembrane domains from human CD8a, and a signaling domain from 4-1BB and CD3ζ (BB3z) (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did not include a control group treated with cyclophosphamide only, and despite they suggested that TLS formation was associated with longer survival; this result was underpowered and biased due to patient selection ( Lutz et al, 2014 ). Recently, Zheng et al (2021) updated the results of this trial after the inclusion of 38 additional patients (87 in total). Combining low dose cyclophosphamide with GVAX promoted worse disease-free survival (arm A × B × C: 18.92 × 8.54 × 5.56 months) and overall survival (34.2 × 15.4 × 16.5) compared to GVAX alone.…”
Section: Clinical Applications and Future Perspectivesmentioning
confidence: 99%
“…Combining low dose cyclophosphamide with GVAX promoted worse disease-free survival (arm A × B × C: 18.92 × 8.54 × 5.56 months) and overall survival (34.2 × 15.4 × 16.5) compared to GVAX alone. Increased density of intratumoral TLS was associated with longer overall survival ( Zheng et al, 2021 ).…”
Section: Clinical Applications and Future Perspectivesmentioning
confidence: 99%